Diagnosis, management of, and return to play guidance for venous thromboembolism in athletes - Brennan Jr, F. H. (Current Sports Medicine Reports, 2022)
Venous thromboembolism (VTE) is not rare and is becoming more recognized in our athletic population. This diagnosis can be elusive. A provider must have a high clinical suspicion and use pretest probabilities to order the appropriate studies and accurately diagnose a VTE. Treatment using direct oral anticoagulants for 3 months is recommended in most cases. Gradual return to play can be achieved after treatment is complete. Some athletes, however, may require lifelong anticoagulation. Return to collision sports may be possible using a timed dose strategy if long-term anticoagulation is needed. The management of an athlete with a VTE should include an individualized treatment plan and involve shared decision making with the athlete, team physicians, and hematologic specialists.